Friction on air wheels: an applicability of Keldysh-Neymark-Fufaev models - Шифрин, Б.М. (Problems of Tribology, 2015)
Y.I. Neymark and N.A. Fufaev have suggested two simplified versions of M.V. Keldysh model for the lateral friction and self-aligning torque calculation provided there is quasi-adhesive tire contact with the support-ing surface. Version (a) is designed for “higher” speed motion and version (b) – for “rigid” air wheels. After the equation have been published by S. Clark group the experiments on the component friction measuring were car-ried out at air wheels harmonic oscillations. In the given article version (a) and (b) theoretical results were compared with S. Clark group experiments. It demonstrated that at “small” S. Clark numbers Keldysh-Neymark-Fufaev equations (b) version gives good re-sults in the part of “lateral force + stabilizing moment” and in the part of “lateral force” – there is S. Clark num-ber changes in the whole range, considered in the present article. Simplified Neymark – Fufaev version (b) can be recommended for use for modelling motion of vehicle systems. For all this either S. Clark numbers or the wheel axle instantaneous speed centre positions have to be controlled. However, the application may appear to be profitable as the motion ranges coverage at which Keldysh-Neymark-Fufaev equations are applicable is sufficiently wide, and the mathematical model simplifica-tion is substantial.